Tocoyena longilobata, a replacement name for Posoqueria speciosa (Gardenieae, Rubiaceae) - Borges, Rodrigo L.; Alves, Maria; Roque, Nádia (Phytotaxa, 2020)
Aublet (1775) described Posoqueria Aublet (1775: 133, tab. 51) and differentiated it from Tocoyena Aublet (1775: 131, tab. 50) by the number of locules of the ovary (unilocular vs. bilocular, respectively) and seed shape (angulate vs. subspherical, respectively). However, in subsequent studies, L.C.M.Richard (1792) and Lamarck (1793) published under Tocoyena certain species that morphologically matched the generic concept of Posoqueria, causing an historical confusion concerning their generic delimitation. Achille Richard (1830), in his Mémoire sur la famille des Rubiacées, synonymized Posoqueria under Tocoyena, a generic delimitation not widely adopted by subsequent authors. For example, Schumann (1889) in Flora Brasiliensis treated Posoqueria and Tocoyena as distinct genera.